2020
DOI: 10.1021/acs.jproteome.0c00219
|View full text |Cite
|
Sign up to set email alerts
|

Macitentan Attenuates Chronic Mountain Sickness in Rats by Regulating Arginine and Purine Metabolism

Abstract: Chronic mountain sickness (CMS) is a high altitude complication with high rates of morbidity and mortality. CMS is characterized by high-altitude polycythemia (HAPC) and high-altitude pulmonary hypertension (HAPH). In this study, macitentan, a dual endothelin receptor antagonist, was used to treat CMS, and the induced metabolomics changes were studied. CMS was induced in rats in a hypobaric hypoxia chamber (simulating a 5500 m plateau) for 4 weeks. Macitentan was administered in the third and fourth weeks (30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Moreover, a study on rats with CMS induced by chronic hypobaric hypoxia (5000 m; 30 days) demonstrated that in the CMS model group, the MDA level was significantly higher than that in the control group, and the concentrations of SOD and GPx were decreased [ 67 ]. Additionally, through a proteomic and metabolomics analysis, a recent study on rats with CMS induced by 28-day exposure to hypobaric hypoxia reported an increase in 8-hydroxyguanosine and trimethylamine N-oxide, which were associated with oxidative stress and pulmonary vasoconstriction processes, respectively [ 68 ] ( Table 1 ).…”
Section: Oxidative Stress and High-altitude Diseasesmentioning
confidence: 99%
“…Moreover, a study on rats with CMS induced by chronic hypobaric hypoxia (5000 m; 30 days) demonstrated that in the CMS model group, the MDA level was significantly higher than that in the control group, and the concentrations of SOD and GPx were decreased [ 67 ]. Additionally, through a proteomic and metabolomics analysis, a recent study on rats with CMS induced by 28-day exposure to hypobaric hypoxia reported an increase in 8-hydroxyguanosine and trimethylamine N-oxide, which were associated with oxidative stress and pulmonary vasoconstriction processes, respectively [ 68 ] ( Table 1 ).…”
Section: Oxidative Stress and High-altitude Diseasesmentioning
confidence: 99%
“…Some evidences show that the prevalence of CMS in high-altitude populations varies from 1.2 to 33% ( Bao et al, 2017 ) and is about 20% among Andean highlanders ( Yao et al, 2018 ). Synchronously, CMS is characterized by high-altitude polycythemia (HAPC) and high-altitude pulmonary hypertension ( Gao et al, 2020 ). Furthermore, patients with HAPC experience venectasia, attention-deficit disorder, and lapse of memory ( Liu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only one amino acid returned to control concentrations >100 days post-LVAD HF. Proline is an important player in glutamate metabolism and, as such, is involved in different signaling pathways, including metabolic reprogramming [43,44], senescence [45], and apoptosis [46,47]. Wang et al recently showed that Pro acts a cardioprotective agent by reducing reactive oxygen species in vitro [48].…”
Section: Discussionmentioning
confidence: 99%